A COMPARATIVE STUDY OF THE INDONESIAN AND ENGLISH VERSIONS OF 'LAUT BERCERITA - Aulia Tsabita Fathiya; Sabrina Faiza Putri; Nesha Atria Navyra; Fairuz Rania Widamulya; Fanya Grace Tahulending; Rina Saraswati S.S, M.Hum.; Pujo Sakti Nur Cahyo S.Hum., M.Hum. (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
Leila S. Chudori's Laut Bercerita explores collective trauma and political oppression in Indonesia, focusing on enforced disappearances during the New Order. This comparative study examines how the Indonesian and English versions convey themes of memory, identity, and justice. Both versions highlight the characters' inner conflicts and the symbolism of the sea and melarung ritual, though these elements carry different cultural nuances. A psychoanalytic analysis reveals how trauma and identity suppression are addressed, with the English version broadening the interpretation to universal psychological themes. Ultimately, the study shows how both versions preserve the core message of resistance while offering distinct cultural perspectives.